The Bahamas : 2022 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for The Bahamas. (IMF Staff Country Reports; Country Report ;, 2022)
The Bahamas is experiencing a tourism-led rebound. Real GDP growth in 2021 was close to 14 percent, as stayover tourist arrivals doubled relative to 2020. The economy is projected to expand by 8 percent in 2022. Nonetheless, it will likely take until 2024 to return to the 2019 level of GDP and the pandemic has given rise to significant human and social costs. The country's medium-term growth challenges are likely worse than before, and public finances are in a more precarious state. Risks are skewed downwards given a difficult near-term financing situation, rising inflationary-and potentially BOP-pressures because of the war in Ukraine, an ongoing threat from the evolving pandemic, and the country's high vulnerability to natural disasters.